Approach to Diagnosis and Management of An Elderly Female Patient with Recurrent Hypocalcemia - Ida Bagus Aditya Nugraha (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2024)
Disorders of calcium metabolism are common in the everyday clinical setting. Although hypocalcemia is not as common as hypercalcemia, it can be life-threatening if not properly recognized and treated promptly. Causes of hypocalcemia can be divided into three broad categories, such as parathyroid hormone (PTH) deficiency, high PTH levels, and other causes. There is no literature that specifically discusses the incidence and prevalence of hypocalcemia in general. In general, renal failure is the most common cause of hypocalcemia. This condition is followed by vitamin D deficiency, magnesium deficiency, acute pancreatitis, and others. The clinical presentation of hypocalcemia can vary widely, from asymptomatic to life-threatening. In an emergency, unrecognized or poorly managed hypocalcemia can cause significant morbidity or mortality. Symptomatic patients with classic clinical findings of acute hypocalcemia require immediate resuscitation and evaluation. However, most cases of hypocalcemia are found based on clinical suspicion as well as appropriate laboratory testing. Treatment of hypocalcemia depends on the presence and severity of symptoms, degree of hypocalcemia, and etiology of hypocalcemia. Most cases of hypocalcemia are clinically mild and require only supportive treatment and further laboratory evaluation. Oral calcium absorption may be indicated for outpatient treatment in mild cases. In cases of severe hypocalcemia leading to seizures, tetany, refractory hypotension, or arrhythmias, a more aggressive approach may be required, including intravenous calcium infusion.